Myocardial and Vascular Involvement in Patients with Takayasu Arteritis: A Cardiovascular MRI Study - Simin Almasi; Sanaz Asadian; Leila Hosseini; Nahid Rezaeian; Shakiba Ghasemi asl; Abdolmohammad Ranjbar; Seyyed-Reza Sadat-Ebrahimi; Behnaz Mahmoodieh; Alireza Salmanipour (Diagnostics, 2023)
We aimed to explore the cardiovascular magnetic resonance (CMR) of Takayasu arteritis (TA) and its cardiovascular complications. CMR was conducted on 37 TA patients and 28 healthy individuals. We evaluated the CMR findings and adverse cardiovascular complications at the time of the CMR (ACCCMR). After 8 to 26 months, the major adverse cardiac and cerebrovascular events (MACCEs) were evaluated. The TA included 25 women (67.6%), aged 36 ± 16 years old, and 28 age- and sex-matched healthy controls. Left ventricular (LV) ejection fraction was significantly lower in the TA group than in the control group (51 ± 9% vs. 58 ± 1.7%; p < 0.001). Aortic mural edema was present in 34 patients (92%) and aortic mural hyperenhancement in 36 (97%). Left ventricular global longitudinal strain (LVGLS) was significantly lower in the TA group (median [interquartile range] = 13.70 [3.27] vs. 18.08 [1.35]; p < 0.001). ACCCMR was seen in 13 TA patients (35.1%), with the most common cardiac complication being myocarditis (16.2%). During a median follow-up of 18 months (8–26 months), nine patients developed MACCEs, of which the most common was cerebrovascular accident in five (13.5%). The LVGLS of the CMR had the strongest association with complications. Myocardial strain values, especially LVGLS, can reveal concurrent and future cardiovascular complications in TA patients.